Leisure and oligarchy: some economic and political traces in Latin America (Impetus, 2021)
This text aims to make an argument from the thesis that in the formation of modern states in the different countries of Latin America, the social political form that emerged was the oligarchic domination, and that was expressed largely through entertainment, but what concocted beyond entertainment was a lazy society that good As it coincides with the origin of property. In this sense, the oligarchy is a “political category” developed permanent practice of “domination” and whose characteristics the concentration of power, a social base reduced, the exclusion of the majority society “mechanisms of political decision” and that is fundamentally “Coercive”. That from a conception of genre entertainment devices concetrar their power and domination.